Effects of travelling speed, reel index and grain moisture content on header losses of a rice combine harvester - Srison, Waree; Chuan-udom, Somchai; Chinsuwan, Winit (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this study was to determine the effects of travelling speed and reel index on harvesting loss of Hommali rice of combine harvester. Four levels of speed of 3, 4, 5, and 6 km/hr, three levels of reel index of 1.5, 3.0, and 4.5 and three levels of grain moisture content of 23.08, 25.20, and 27.02% wb were used for studying. The results indicated that the travelling speed of 5 km/hr, reel index of 3.0 and grain moisture content of 23.08% wb or 32 day after heading was considered to be appropriated for harvesting Hommali rice.